Evaluating the Impact of Goal Setting on Improving Diet Quality in Chronic Kidney Disease - Chan, Chi H.; Conley, Marguerite; Reeves, Marina M.; Campbell, Katrina L.; Kelly, Jaimon T. (Frontiers in Nutrition, 2021)
Background: Improving diet quality in chronic kidney disease (CKD) is challenging due to a myriad of competing recommendations. Patient-centered goal setting can facilitate dietary behavior change, however, its role in improving diet quality in CKD has not been investigated. Aim: To evaluate the effects of goal setting on improving diet quality in stage 3-4 CKD. Methods: Forty-one participants completed a six-month dietitian-led telehealth (combined coaching calls and text-messages) intervention as part of a larger RCT. Participants set one to two diet-related SMART goals and received weekly goal tracking text-messages. Dietary intake was assessed using the Australian Eating Survey at baseline, three, and six-month, with diet quality determined using the Alternate Healthy Eating Index (AHEI). Results: Significant improvements in AHEI (+6.9 points; 95% CI 1.2 to 12.7), vegetable (+1.1 serves; 95% CI 0.0 to 2.3) and fiber intake (+4.2 grams; 95% CI 0.2 to 8.2) were observed at three months in participants setting a fruit and/or vegetable goal, compared to those who did not. However, no significant or meaningful changes were observed at six months. No other goal setting strategy appeared in effect on diet intake behavior or clinical outcomes in this group of CKD participants. Conclusions: Patient-centered goal setting, particularly in relation to fruit and vegetable intake, as part of a telehealth coaching program, significantly improved diet quality (AHEI), vegetable and fiber intake over three months. More support may be required to achieve longer-term behavior change in stage 3-4 CKD patients.